Disturbed sleep is associated with increased C-reactive protein in young women - Okun, Michele L. (2008)
Evidence links disturbed sleep with an exaggerated inflammatory response and increased risk of adverse health outcomes. An emerging risk factor for many adverse health outcomes is chronic, low-grade inflammation. An exaggerated inflammatory response could provide a biological link between disturbed sleep and adverse health outcomes. The relationship between sleep and chronic, low-grade inflammation has been sparsely examined in otherwise healthy, young women. We evaluated cross-sectional relationships between self-reported sleep and three inflammatory markers. Participants were community dwelling nonpregnant women (N = 43, 28.2 ± 5.2 years of age). Measures included the Pittsburgh Sleep Quality Index (PSQI), sleep diaries, and serum levels of IL-6, TNF-α and C-reactive protein. Poor sleep quality and continuity were associated with higher CRP levels after controlling for covariates. No significant relationships were observed between PSQI scores and IL-6 or TNF-α; sleep duration was not related to any of the inflammatory markers. Poor sleep, in young adulthood, may contribute to the chronic, low-grade inflammation associated with an increased risk for future adverse health outcomes. Future work should longitudinally evaluate how these relationships may affect development of gender-specific diseases in apparently healthy young women.